2002
DOI: 10.1111/j.1475-2743.2002.tb00258.x
|View full text |Cite
|
Sign up to set email alerts
|

The use of a nitrification inhibitor, dicyandiamide (DCD), to decrease nitrate leaching and nitrous oxide emissions in a simulated grazed and irrigated grassland

Abstract: Abstract. In grazed dairy pasture systems, a major source of NO3– leached and N2O emitted is the N returned in the urine from the grazing animal. The objective of this study was to use lysimeters to measure directly the effectiveness of a nitrification inhibitor, dicyandiamide (DCD), in decreasing NO3– leaching and N2O emissions from urine patches in a grazed dairy pasture under irrigation. The soil was a free‐draining Lismore stony silt loam (Udic Haplustept loamy skeletal) and the pasture was a mixture of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
164
4
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 260 publications
(190 citation statements)
references
References 31 publications
20
164
4
2
Order By: Relevance
“…This may be related to differences in management practices and environmental conditions between the studies which ranged from temperate (current study) to subtropical to Mediterranean climates. In the current study the nitrification inhibitor DCD was incorporated into the urea granule at manufacture which provided a very 22 targeted delivery compared with spraying a liquid solution of DCD onto the whole paddock (Di and Cameron, 2002;. Comparisons of granular versus liquid DCD application at the same time and rate found no effect of formulation on N leaching or yield (Menneer et al, 2008).…”
Section: The Effect Of N Formulation On N 2 O Emissionsmentioning
confidence: 81%
“…This may be related to differences in management practices and environmental conditions between the studies which ranged from temperate (current study) to subtropical to Mediterranean climates. In the current study the nitrification inhibitor DCD was incorporated into the urea granule at manufacture which provided a very 22 targeted delivery compared with spraying a liquid solution of DCD onto the whole paddock (Di and Cameron, 2002;. Comparisons of granular versus liquid DCD application at the same time and rate found no effect of formulation on N leaching or yield (Menneer et al, 2008).…”
Section: The Effect Of N Formulation On N 2 O Emissionsmentioning
confidence: 81%
“…Published research in 2002 first showed its potential effectiveness in Canterbury to reduce nitrate leaching and nitrous oxide emissions within urine patches (Di & Cameron 2002, 2005. It was also noted that in reducing losses of urine-N to both processes, there is an increased potential for the retained N to increase dry matter (DM) production and reduce N fertiliser application, thereby increasing farming efficiency and productivity.…”
Section: Introductionmentioning
confidence: 99%
“…However, in soils ammonium may be converted into mobile nitrate ions within a short period of time. Therefore nitrification inhibitors stabilized N fertilizers, for example, ammonium sulphate nitrate with the nitrification inhibitor 3,4-dimethylpyrazol phosphate (DMPP), were introduced (Di andCameron 2002, Benckiser et al 2013). Controlling the microbiological process of nitrification, nitrate losses could be reduced by increasing the assimilated N by plants (Subbarao et al 2006).…”
mentioning
confidence: 99%